Cloning, sequencing and functional analysis of the chicken tyrosine gene promoter - Ferguson, Christine Anne (Department of Human Biology, 2017)
The differentiation of melanocytes from multipotential neural crest cells is an ideal system for studying the processes underlying lineage determination in development. Tyrosinase is a key enzyme in melanin biosynthesis and the activation of the tyrosinase gene is characteristic of differentiated melanocytes. In order to study the mechanisms underlying activation of melanocyte-specific genes during differentiation in chick embryos, a chicken genomic DNA library was screened for tyrosinase-encoding sequences using a mouse tyrosinase cDNA probe. Two identical hybridising clones were identified. Restriction mapping and sequencing revealed that both clones contained a 4.3 kb genomic DNA fragment, CTYR4.3, that included 2125 nt of the 5' flanking region, the first exon and part of the first intron of the chicken tyrosinase gene. The 5' flanking sequence of CTYR4.3, which is the most extensive to be reported for a lower vertebrate tyrosinase gene to date, was analysed further using computer-aided homology searches and primer extension. Alignment of the promoter sequences of CTYR4.3 with those of the human, mouse, quail and turtle tyrosinase genes revealed two evolutionary conserved regions. These regions may be functionally significant as they contain regulatory elements previously reported to play a role in melanocyte-specific expression of the tyrosinase gene in mammals. These include an initiator region and an associated SP1-binding site, the M-box and an upstream enhancer element, TDE. In addition, other potential transcription factor binding motifs were identified, including an AP-1-binding site, a UV-responsive element and glucocorticoid-responsive elements. Although several TATA box motifs were identified, they were situated more than 200 bp upstream of the transcription start sites mapped by primer extension analysis and therefore are unlikely to function as TFIID-binding sites. Transcription initiation appears to occur at heterogeneous start sites, and given the absence of a functional TATA box, may be mediated via the conserved initiator region and SP1-binding site. To test the ability of the 5' flanking sequence of CTYR4.3 to drive transcription and to begin to assess the functional significance of the various conserved elements, transient transfection assays were carried out. Constructs were generated in which 2.1 kb, 1.1 kb, 0.5 kb and 0.2 kb fragments of the 5' flanking sequence were linked to a luciferase reporter gene. These constructs were introduced into cultures of chicken retinal pigment epithelial cells (RPE), immortalised quail neural crest cells (MQTNC), and human liver cells (Hep G2) by calcium phosphate-mediated transfection. Transfections with all constructs resulted in luciferase activities significantly greater than those that were observed with the promoterless luciferase construct, thus confirming that the 5' flanking sequence of CTYR4.3 does possess promoter activity. However, the level of expression from the various constructs differed markedly in the different cell types. In the tyrosinase-negative Hep G2 cells, low levels of expression were observed with all constructs. In the tyrosinase-positive RPE cells, a high level of luciferase activity was obtained specifically with the smallest (0.2 kb) promoter construct. Since the 0.2 kb promoter fragment does not include the conserved initiator region, SP1-binding site, or M-box, the role of these elements in tissue-specific transcription initiation of the chicken tyrosinase gene is now questionable. These results suggest the existence of transcription regulatory mechanisms that are unique to avians and possibly other lower vertebrates. In contrast to the results obtained for RPE cells, the highest luciferase activity was obtained with the full length 2.1 kb promoter construct in the immortalised quail neural crest-derived cells. These results may have developmental significance since they suggest that the chicken tyrosinase gene promoter is regulated differently in RPE cells and neural crest-derived cells.